Gastroenterology and Neurology. Issue 3 (June 2017) - Pfeiffer, Ronald F.
Abstract : ABSTRACT: Purpose of Review: Just as gastrointestinal dysfunction may develop in the setting of neurologic disease, neurologic dysfunction may become evident in the setting of gastrointestinal disease. This article describes the range of neurologic features that have been described in three primary gastrointestinal diseases: celiac disease and gluten-related disorders, inflammatory bowel disease, and Whipple disease. Particular emphasis is placed on the controversial and evolving clinical picture of neurologic dysfunction in disorders of gluten sensitivity. Recent Findings: Gluten-related disorders, including both the traditional autoimmune-based celiac disease and the more recently recognized nonautoimmune, nonallergic gluten sensitivity, have been the source of much attention in both medical and lay publications. The possible association between Crohn disease and neurologic disorders also is receiving attention. The recognition that, although Whipple disease is an exceedingly rare disorder, a surprising percentage of the population may be asymptomatic stool carriers of the causative organism makes it important to always be cognizant of the disorder. Summary: The range of neurologic dysfunction in gastrointestinal diseases is broad and spans the spectrum from peripheral to central processes. Peripheral neuropathy, myopathy, myelopathy, cerebrovascular events, epilepsy, encephalopathy, and cerebellar dysfunction have all been described. Neurologists should be aware of the possibility that an underlying gastrointestinal disease process may be present in and responsible for the neurologic dysfunction that has prompted referral of an individual for evaluation.